Erythema nodosum po salmonelové gastroenteritidĕ - Rucki, S (Ceskoslovenska pediatrie, 1993)
The author describes a case of erythema nodosum which developed after Salmonella gastroenteritis in a 7,5-year-old boy. Other known causes of this skin lesion are discussed.
Keywords: erythema nodosum; Salmonella Infections; Erythema Nodosum; mužské pohlaví; salmonelóza; gastroenteritida; Humans; Male; Gastroenteritis; dítě; lidé; Salmonella enteritidis; Child